Environmental monitoring and analysis of quality of the Nizhny Novgorod region ground water with the development of the technologies of their filtration - Kuberis Eduard Alexandrovich; Gorbachov Evgeny Alekseevich (Zbornik Radova: Geografski institut "Jovan Cvijić", 2014)
This article provides the analysis of the quality of underground water sources of the Nizhny Novgorod region, the necessity of improving of the iron removal and demanganation installations for groundwater treatment. The research data to find the most effective method for iron removal and water demanganation using experimental pilot installation in natural conditions are presented.